2016
DOI: 10.1002/ajmg.a.37564
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the genetic basis of 3MC syndrome: Findings in 12 further families

Abstract: The 3MC syndromes are a group of rare autosomal recessive disorders where the main clinical features are cleft lip and palate, hypertelorism, highly arched eyebrows, caudal appendage, postnatal growth deficiency, and genitourinary tract anomalies. Ophthalmological abnormalities, most notably anterior chamber defects may also be seen. We describe the clinical and molecular findings in 13 individuals with suspected 3MC syndrome from 12 previously unreported families. The exclusion of the MASP1 and COLEC11 Loci i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…Sequence analyses of DNA from multiple families of various ethnic backgrounds identified mutations in genes collectin‐11 ( COLEC11 ) and mannose‐binding lectin‐associated serine protease 1 ( MASP1 ), each of which encodes a component of the lectin complement pathway (Rooryck et al, ). However, mutations in the COLEC11 and MASP1 genes have not been found in other 3MC families, suggesting that an additional layer of genetic heterogeneity exists (Urquhart et al, ).…”
Section: Use Of Zebrafish To Explore the Developmental Functions Of Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analyses of DNA from multiple families of various ethnic backgrounds identified mutations in genes collectin‐11 ( COLEC11 ) and mannose‐binding lectin‐associated serine protease 1 ( MASP1 ), each of which encodes a component of the lectin complement pathway (Rooryck et al, ). However, mutations in the COLEC11 and MASP1 genes have not been found in other 3MC families, suggesting that an additional layer of genetic heterogeneity exists (Urquhart et al, ).…”
Section: Use Of Zebrafish To Explore the Developmental Functions Of Gmentioning
confidence: 99%
“…Sequence analyses of DNA from multiple families of various ethnic backgrounds identified mutations in genes collectin-11 (COLEC11) and mannose-binding lectin-associated serine protease 1 (MASP1), each of which encodes a component of the lectin complement pathway (Rooryck et al, 2011). However, mutations in the COLEC11 and MASP1 genes have not been found in other 3MC families, suggesting that an additional layer of genetic heterogeneity exists (Urquhart et al, 2016). In zebrafish embryos, colec11 is expressed in the pronephric duct, glomeruli, and cranial paraxial mesendoderm (Rooryck et al, 2011), and both colec11 morphants and colec11/masp1 double morphants exhibit cleft palate.…”
Section: Carnevale Mingarelli Malpuech and Michels Syndromesmentioning
confidence: 99%
“…Homozygous mutations have been identified in MASP1 in individuals with Carnevale, Malpuech, and Michels syndrome [Rooryck et al, 2011;Atik et al, 2015;Urquhart et al, 2016]. These syndromes contribute to the 3MC syndrome (OMIM 257920).…”
Section: Masp1mentioning
confidence: 99%
“…3MC syndrome is an autosomal recessive heterogeneous disorder with features linked to developmental abnormalities. The main features include facial dysmorphism, craniosynostosis, cleft lip/palate high-arched eyebrows, hypertelorism, developmental delay, and hearing loss [Urquhart et al, 2016]. Besides MASP1 , COLEC11 has been identified as a genetic cause of 3MC syndrome.…”
Section: Masp1mentioning
confidence: 99%
“…Mutations in these genes contribute to the pathogenesis of 3MC syndrome [Rooryck et al, 2011;Urquhart et al, 2016;Munye et al, 2017] which is the collective term for multiple related syndromes (Carnevale, Mingarelli, Malpuech, and Michels syndromes) [Titomanlio et al, 2005]. Common clinical features include craniosynostosis, cleft palate, hypertelorism, hearing deficits, growth deficiencies, and heart defects [Titomanlio et al, 2005], which are consequently suggested to be affected during development by abrogation to cytokine signalling [Newton and Dixit, 2012].…”
Section: Masp1 and Colec11mentioning
confidence: 99%